William Branford Shubrick correspondence - Shubrick, William Branford, 1790-1874.
ALS (1863 June 23) from Shubrick to an unknown recipient in which he summarizes his naval career with particular emphasis on naval operations during the War of 1812 and Mexican War and the success of a mission (1858) to Paraguay.
Naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Navy -- History; Mexican War, 1846-1848 -- Naval operations, American; Paraguay -- Foreign relations -- United States; United States -- History -- War of 1812 -- Naval operations; United States -- Foreign relations -- Paraguay; Naval officers